Experimental study of the performance of a double-source heat-pipe composite vapour-compression heating unit. (October 2017) - Han, Zongwei; Ju, Xiaomei; Qu, Lejian; Liu, Jiangzhen; Ma, Xiao; Zhang, Shuiwei
Highlights: A double-source heat-pipe composite vapour-compression heating unit is set up. The performance of the unit under the two operating conditions is investigated. The effect of various parameters on the performance of the unit has been analysed. Abstract: In order to make heat pump systems more stable with efficient and economical operation under heating conditions in cold regions, a multi-source coupled heat pump system is proposed. The main core part of the system is a double-source heat-pipe composite vapour-compression heating unit. An experimental study on the performance of the unit under the operating conditions of a heat pipe and vapour compression is carried out under different meteorological parameters and test conditions. The results show that solar radiation significantly improves the performance of the unit. The average heat capacity and COP of the unit can be increased by 27.61 and 27.85% respectively under the heat pipe operating condition and by 5.14 and 4.90% respectively under the vapour compression operating condition. Meanwhile, the effects of outdoor temperature and water inlet temperature on the performance are analysed. When the outdoor temperature increases from 23 to 28 °C, the COP of the heat pipe operating condition changes from 7.86 to 10.62. When the outdoor temperature drops from −2 to −16 °C, the COP of the two-stage compression under the vapour injection heating condition changes from 2.50 to 2.12. It can be seen that the unit can ensure continuous and efficient operation of the multi-source coupled heat pump system.